Nursing Home Aversion Post-Pandemic: Implications for Savings and Long-Term Care Policy - Bertrand Achou; Philippe De Donder; Franca Glenzer; Minjoon Lee; Marie-Louise Leroux (Center for Economic Studies and ifo Institute (CESifo), 2021)
COVID-19 outbreaks at nursing homes during the recent pandemic, which received ample media coverage, may have lasting negative impacts on individuals' perceptions regarding nursing homes. We argue that this could have sizable and persistent implications for savings and long-term care policies. We first develop a theoretical model predicting that higher nursing home aversion should induce higher savings and stronger support for policies subsidizing home care. We further document, based on a survey on Canadians in their 50s and 60s, that higher nursing home aversion is widespread: 72% of respondents are less inclined to enter a nursing home because of the pandemic. Consistent with our model, we find that the latter are much more likely to have higher intended savings for older age because of the pandemic. We also find that they are more likely to strongly support home care subsidies.
Keywords: D14; H31; H51; H53; I10; I31; 330; pandemic risk; nursing home; long-term care; savings; public policy